Metagenomic Analysis of Fish-Associated Ca. Parilichlamydiaceae Reveals Striking Metabolic Similarities to the Terrestrial Chlamydiaceae. (7th September 2018) - Taylor-Brown, Alyce; Pillonel, Trestan; Greub, Gilbert; Vaughan, Lloyd; Nowak, Barbara; Polkinghorne, Adam
Abstract: Chlamydiae are an example of obligate intracellular bacteria that possess highly reduced, compact genomes (1.0–3.5 Mbp), reflective of their abilities to sequester many essential nutrients from the host that they no longer need to synthesize themselves. The Chlamydiae is a phylum with a very wide host range spanning mammals, birds, fish, invertebrates, and unicellular protists. This ecological and phylogenetic diversity offers ongoing opportunities to study intracellular survival and metabolic pathways and adaptations. Of particular evolutionary significance are Chlamydiae from the recently proposed Ca. Parilichlamydiaceae, the earliest diverging clade in this phylum, species of which are found only in aquatic vertebrates. Gill extracts from three Chlamydiales -positive Australian aquaculture species (Yellowtail kingfish, Striped trumpeter, and Barramundi) were subject to DNA preparation to deplete host DNA and enrich microbial DNA, prior to metagenome sequencing. We assembled chlamydial genomes corresponding to three Ca . Parilichlamydiaceae species from gill metagenomes, and conducted functional genomics comparisons with diverse members of the phylum. This revealed highly reduced genomes more similar in size to the terrestrial Chlamydiaceae, standing in contrast to members of the Chlamydiae with a demonstrated cosmopolitan host range. We describe a reduction in genes encoding synthesis of nucleotides and amino acids, among other nutrients, and an enrichment of predicted transport proteins. Ca . Parilichlamydiaceae share 342 orthologs with other chlamydial families. We hypothesize that the genome reduction exhibited by Ca. Parilichlamydiaceae and Chlamydiaceae is an example of within-phylum convergent evolution. The factors driving these events remain to be elucidated.